Music therapy as an early intervention to prevent chronification of tinnitus - Grapp, Miriam; Hutter, Elisabeth; Argstatter, Heike; Plinkert, Peter K.; Bolay, Hans V. (International journal of clinical and experimental medicine, 2013)
In the present study a music therapeutic intervention according to the ‘Heidelberg Model’ was evaluated as a complementary treatment option for patients with acute tinnitus whom medical treatment only brought minimal or no improvement. The central question was if music therapy in an early phase of tinnitus was able to reduce tinnitus symptoms and to prevent them from becoming chronical. 23 patients with acute tinnitus (6-12 weeks) were included in this study and took part in our manualized short term music therapeutic treatment which lasted ten consecutive 50-minutes sessions of individualized therapy. Tinnitus severity and individual tinnitus related distress were assessed by the Tinnitus Beeinträchtigungs-Fragebogen (i.e. Tinnitus Impairment Questionnaire, TBF-12) at baseline, start of treatment, and end of treatment. Score changes in TBF-12 from start to end of the treatment showed significant improvements in tinnitus impairment. This indicates that this music therapy approach applied in an initial stage of tinnitus can make an important contribution towards preventing tinnitus from becoming a chronic condition.
Gesehen am 25.02.2020